Testing the Level of Alternative Institutions as a Slowdown Factor of Economic Development: the Case of Montenegro - Mimo Draškovic; Sanja Bauk; Dalia Streimikiene; Veselin Draskovic (Amfiteatru Economic Journal, 2017)
The purpose of the article is to test public's perception of the opportunistic behavior and alternative institutions existence and the degree of their influences on reproduction of the economic crisis. For that purpose, besides the theoretical considerations, the paper comprises quantitative analysis of affecting the inability of economic development, and reproduction of crisis, by the following factors: (a) non-market enrichment and log-rolling structures, (b) parties' monopolies and lobbyism, and (c) systemic corruption. Multiple regression linear approach is applied on a sample of 300 selected respondents in five towns in Montenegro: Podgorica, Niksic, Cetinje, Herceg Novi, and Kotor. On the basis of the conducted statistical examines: standard error of the regression estimate, correlation coefficient, and coefficient of determination are calculated on the basis of previously determined regression coefficients and forecast values of the linear function of free variables (factors: a, b, and c). The regression plots for each of the considered cases, which verify the starting hypothesis, are shown along with the discussion and conclusions. Our results indicate the need to reduce and eliminate effects of the above factors in the society and economy, since they represent concrete manifestations of alternative institutions' negative impacts. The main conclusion of the research is that the authorities in Montenegro should identify all of the channels through which alternative inst itutions do affect the reduction of social and economic choices. In this sense, it is proposed overcoming the monistic neoliberal policies, along with affirmation of institutional pluralism.
Keywords: E26; O17; P37; C25; 330; alternative institutions; quasi-institutional monism; institutional pluralism; multiple regression linear approach